A Guide to Good Reasoning Cultivating Intellectual Virtues - Wilson, David C. (Open textbook library., 1999)
A Guide to Good Reasoning has been described by reviewers as “far superior to any other critical reasoning text.” It shows with both wit and philosophical care how students can become good at everyday reasoning. It starts with attitude—with alertness to judgmental heuristics and with the cultivation of intellectual virtues. From there it develops a system for skillfully clarifying and evaluating arguments, according to four standards—whether the premises fit the world, whether the conclusion fits the premises, whether the argument fits the conversation, and whether it is possible to tell.